2019
DOI: 10.3390/s19112495
|View full text |Cite
|
Sign up to set email alerts
|

An Recognition–Verification Mechanism for Real-Time Chinese Sign Language Recognition Based on Multi-Information Fusion

Abstract: For online sign language recognition (SLR) based on inertial measurement unit (IMU) and a surface electromyography (sEMG) sensor, achieving high-accuracy is a major challenge. The traditional method for that is the segmentation–recognition mechanism, which has two key challenges: (1) it is difficult to design a highly robust segmentation method for online data with inconspicuous segmentation information; and (2) the diversity of input data will increase the burden of the classification. The recognition–verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…These results indicated that the method of combing FRET imaging with batch processing was time-saving, simply and efficient to perform without the need for expertise, and saved the time and became more pronounced as the number of counted cells increased. It was worth mentioning that the batch processing could speed up the operation [29]. Our results also confirmed it.…”
Section: Batch Processing Of Fret Efficiency Values On Cell Membranesupporting
confidence: 86%
“…These results indicated that the method of combing FRET imaging with batch processing was time-saving, simply and efficient to perform without the need for expertise, and saved the time and became more pronounced as the number of counted cells increased. It was worth mentioning that the batch processing could speed up the operation [29]. Our results also confirmed it.…”
Section: Batch Processing Of Fret Efficiency Values On Cell Membranesupporting
confidence: 86%
“…e convolution operation is included in the activation function, as shown in formula (7) [21], to reduce the amount of computation of the network and avoid the over-fitting phenomenon.…”
Section: Design Of Watercolor Cultural and Creative Products Based On...mentioning
confidence: 99%
“…The Myo armband is a lightweight off-the-shelf wearable device providing nine inertial and eight-channel EMG signals. Many studies on sign language word and gesture recognition have used this device considering the portability of the armband [ 9 , 10 , 11 , 12 , 13 ]. Savur & Sahin [ 14 ] classified the gestures of 26 English alphabet letters with Myo armband.…”
Section: Introductionmentioning
confidence: 99%